Are ethical and social banks less risky? Evidence from a new dataset - Marlene Karl (WWWforEurope, 2015)
This paper introduces a new and comprehensive dataset on “alternative” banks in EU and OECD countries. Alternative banks (e.g. ethical, social or sustainable banking) experienced a recent increase in media interest and have been hailed as an answer to the financial crisis but no research exists on their stability. This paper studies whether alternative banks differ from conventional banks in terms of riskiness. For this I construct a comprehensive dataset of alternative banks and compare their riskiness with an adequately matched control group of conventional banks using mean comparison and panel regression techniques. The main result is that alternative banks are significantly more stable (in terms of z-score) than their conventional counterparts. The results are robust to different estimation methods and data specifications. Alternative banks also have lower loan to asset ratios and higher customer deposit ratios than conventional banks.
Keywords: G21; G32; E44; M14; 330; Ethical banking; social banking; bank risk; financial crisis